1992
DOI: 10.1159/000468781
|View full text |Cite
|
Sign up to set email alerts
|

Functional Hepatocellular Heterogeneity for the Production of Plasma Proteins

Abstract: It is now well established that hepatocytes are the main liver cells responsible for the synthesis of plasma proteins produced by the liver. That these cells are not specialized in the production of the different plasma proteins is also well established. Presently the point still debated is whether a functional hepatocellular heterogeneity exists for plasma protein synthesis as for many other hepatocyte functions. Several physiological and pathological situations suggest that this heterogeneity takes place in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Also, both the basal and inflammation-induced expression of acute-phase proteins is distributed heterogeneously along the liver lobule. Whereas a,-macroglobulin, a,-inhibitor, fibrinogen and a,-acid glycoprotein are expressed mainly in the periportal zone, a-fetoprotein and a2,macroglobulin are expressed predominantly in the perivenous zone (47). Thus the inhibition during the IL-6-mediated inflammatory response of PCK gene expression mainly in the periportal zone and of GK gene expression mainly in the perivenous zone appears functionally necessary.…”
Section: Discussionmentioning
confidence: 95%
“…Also, both the basal and inflammation-induced expression of acute-phase proteins is distributed heterogeneously along the liver lobule. Whereas a,-macroglobulin, a,-inhibitor, fibrinogen and a,-acid glycoprotein are expressed mainly in the periportal zone, a-fetoprotein and a2,macroglobulin are expressed predominantly in the perivenous zone (47). Thus the inhibition during the IL-6-mediated inflammatory response of PCK gene expression mainly in the periportal zone and of GK gene expression mainly in the perivenous zone appears functionally necessary.…”
Section: Discussionmentioning
confidence: 95%
“…1992), xenobiotics Traber 1989), bile acids (Groothuis and Meijer 1992) and plasma proteins (Feldmann et al 1992) as well as the diverse functions of the various non-parenchymal cells (Bouwens et al 1992). The present article attempts to update the previous review on the zonation of metabolism and especially of gene expression.…”
Section: 1mentioning
confidence: 99%
“…Previous results have demonstrated that localization of the hepatocyte within the liver is strictly associated with the levels of synthesis of certain plasma proteins, such as albumin. Hepatocytes localized in the periportal area of the liver produce higher levels of albumin, compared to hepatocytes situated in other lobular zones [197][198][199]. These studies thus provided compelling evidence that MSC represent a valuable source of cells for liver repair and regeneration and demonstrate that, by altering the site of injection, generation of hepatocytes occurs in different hepatic zones, and the resultant hepatocytes exhibit differing functionality, just like their naturally-occurring counterparts.…”
Section: Results Obtained In Fetal Sheep Modelmentioning
confidence: 90%